Penerapan Sistem Merit dalam Mutasi Jabatan Pegawai Negeri Sipil di Kantor Camat Sungai Beremas Kabupaten Pasaman Barat - Permata, Dwi; Mubarak, Adil (PUBLICNESS: Journal of Public Administration Studies, 2023)
This research aim of being able to describe how the Implementation of the Merit System in Transfers of Civil Servant Positions at the Sungai Beremas Sub-district Office, West Pasaman Regency and to find out the Inhibiting Factors and Also whether there are supporting factors in the implementation of the System the merits. The application of the merit system at the Sungai Beremas Subdistrict Office, Pasaman Regency in implementing promotion of positions prioritizes employees who have managerial competence and technical competence. Promotions are given to employees who have above average abilities. It is hoped that this will provide competition for employees to improve performance in their respective work units at the Sungai Beremas District Office, Pasaman Regency. The obstacle faced in the implementation of the Merit System in Sungai Beremas District, West Pasaman Regency, is the replacement of the Head of Sub-District Head at the Sungai Beremas District Office, Pasamanya Regency, once every 5 years. With the substitution of this Camat, of course there will be other management changes. Then the Camat's Commitment as PPK emphasizes loyalty rather than qualifications, education, competence and performance. So that sometimes employees do not know their main duties, because they are not experts in the field, with the Camat's commitment as PPK which places more emphasis on loyalty than qualifications, education, competence and performance.